Aplikasi Mobile Presensi Siswa Terintegrasi SMS Gateway Menggunakan Algoritma Breadth-First Search (BFS) - Humansyah, Hanggita Ahmad; Fitri, Iskandar; Rubhasy, Albaar (KITA Institut, 2021)
Teacher attendance or student absenteeism is currently carried out manually. Therefore, researchers developed an Android-based application, with the aim of making it easier for teachers to carry out the student attendance process. This system is equipped with an SMS Gateway. So that with the system created, parents can monitor the attendance of their children in the course and training institutions. The SMS system gateway has an auto-response facility and by adopting an application from the Gammu system to bridge the SMSÂ database Gateway to convey data to the SMS device using one of the search methods, namely the first wide search method, breadth-first search with reading and looking for connected data one by one. to data communication client-server. Using JSON as data exchange between the Android application and the web server for the student database. From the results of the tests that have been carried out, this student attendance application runs as desired with existing functions.Keywords:SMS Gateway, Android, Attendance, Breadth-First Search, Gammu.